2022
DOI: 10.1007/s12646-022-00641-2
|View full text |Cite
|
Sign up to set email alerts
|

Courage: A Potential Mediator of the Relationship Between Personality and Social Anxiety

Abstract: Social anxiety is one of the most prevalent and chronic mental-health conditions in young adults. To date, no studies have been conducted about the relationships between the Big Five personality dimensions, courage, and social anxiety among Malaysian undergraduate students. Therefore, this study was designed to examine courage as a potential mediator of the association between the Big Five personality dimensions and social anxiety among Malaysian Undergraduates. In this study, 500 Malaysian undergraduate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Experiences of traumatic events and adverse life events suffered in childhood have a profound impact on individuals. They become more fearful of interacting with people, fear being judged, have a negative, skeptical attitude toward themselves, and do not participate in as many social activities [ 50 , 51 ]. The findings also showed that extraversion was negatively related to social anxiety; this is consistent with previous studies [ 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences of traumatic events and adverse life events suffered in childhood have a profound impact on individuals. They become more fearful of interacting with people, fear being judged, have a negative, skeptical attitude toward themselves, and do not participate in as many social activities [ 50 , 51 ]. The findings also showed that extraversion was negatively related to social anxiety; this is consistent with previous studies [ 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…They become more fearful of interacting with people, fear being judged, have a negative, skeptical attitude toward themselves, and do not participate in as many social activities [ 50 , 51 ]. The findings also showed that extraversion was negatively related to social anxiety; this is consistent with previous studies [ 50 , 52 ]. Highly extroverted people tend to be sociable, talkative, enthusiastic, and confident [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one possibility on buffering stress is that courage might positively linked with a self-directed coping (i.e., having a positive attitude to problem-solving) whereas negatively predicted with self-avoidant coping (i.e., using avoidance strategies and having a transcendent orientation). It acts on coping by activating psychological resources that can help actors to sustain and persevere, which can manage effectively and surmount the damage to cognitive function under conditions of stress ( Magnano et al, 2017 ; Abdollahi et al, 2022 ). Besides, hardiness, as a pattern of courage and strategy that facilitates turning stressful circumstances from potential threats into growth opportunities by developing 3C’s (i.e., challenge, commitment, control) hardy coping, social support and self-care ( Maddi, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…People's unconscious attitude towards the environment is posing a measure threat to livable existence. Environmental pollution is a universal problem and its potential to affect the health of human beings is great (Fereidoun et al, 2007;Adusumalli, 2016;Abdollahi et al, 2022). World is becoming a worse place for its habitat.…”
Section: Introductionmentioning
confidence: 99%